2015
DOI: 10.1016/j.pbb.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Repeated estradiol benzoate treatment protects against the lordosis-inhibitory effects of restraint and prevents effects of the antiprogestin, RU486

Abstract: The following experiment was designed to test two specific questions: (1) Does the antiprogestin, RU486, reduce emergence of lordosis behavior and/or proceptivity in rats given repeated treatment with 10 μg estradiol benzoate (EB) and/or a single high dose (40 μg) of EB? (2) Does RU486 accentuate the effects of a 5 min restraint experience on sexual behaviors in rats given repeated treatment with estradiol benzoate (EB) and/or a high dose of EB? RU486 was used to determine if a high dose and/or repeated treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…In recent years, adenomyosis clinical studies have found that mifepristone can play a role in inhibiting ovulation and directly affects the progesterone receptor, which prevents the proliferation and differentiation of ectopic endometrium, reducing its growth potential and making it shrink [37,38] . Further experimental studies have found that mifepristone can inhibit ectopic endometrial angiogenesis and simultaneously promote ectopic endometrial apoptosis [20,39] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, adenomyosis clinical studies have found that mifepristone can play a role in inhibiting ovulation and directly affects the progesterone receptor, which prevents the proliferation and differentiation of ectopic endometrium, reducing its growth potential and making it shrink [37,38] . Further experimental studies have found that mifepristone can inhibit ectopic endometrial angiogenesis and simultaneously promote ectopic endometrial apoptosis [20,39] .…”
Section: Discussionmentioning
confidence: 99%